Identifying gravity waves launched by the Hunga Tonga-Hunga Ha′apai volcanic eruption in mesosphere/lower-Thermosphere winds derived from CONDOR and the Nordic Meteor Radar Cluster - G Stober; A Liu; A Kozlovsky; Z Qiao; W Krochin; G Shi; J Kero; M Tsutsumi; N Gulbrandsen; S Nozawa; M Lester; K Baumgarten; et al. (2023)
The Hunga Tonga-Hunga Ha′apai volcano eruption was a unique event that caused many atmospheric phenomena around the globe. In this study, we investigate the atmospheric gravity waves in the mesosphere/lower-Thermosphere (MLT) launched by the volcanic explosion in the Pacific, leveraging multistatic meteor radar observations from the Chilean Observation Network De Meteor Radars (CONDOR) and the Nordic Meteor Radar Cluster in Fennoscandia. MLT winds are computed using a recently developed 3DVAR+DIV algorithm. We found eastward-and westward-Traveling gravity waves in the CONDOR zonal and meridional wind measurements, which arrived 12 and 48ĝ€¯h after the eruption, and we found one in the Nordic Meteor Radar Cluster that arrived 27.5ĝ€¯h after the volcanic detonation. We obtained observed phase speeds for the eastward great circle path at both locations of about 250ĝ€¯mĝ€¯s-1, and they were 170-150ĝ€¯mĝ€¯s-1 for the opposite propagation direction. The intrinsic phase speed was estimated to be 200-212ĝ€¯mĝ€¯s-1. Furthermore, we identified a potential lamb wave signature in the MLT winds using 5ĝ€¯min resolved 3DVAR+DIV retrievals.